2020
DOI: 10.1109/access.2020.3005450
|View full text |Cite
|
Sign up to set email alerts
|

A New Image Recognition and Classification Method Combining Transfer Learning Algorithm and MobileNet Model for Welding Defects

Abstract: Welding quality directly affects the welding structure's service performance and life. Hence, the effective monitoring welding defects is essential to ensure the quality of the weld structure. Owing to the non-uniformity of the shape, position and size of welding defects, it is a complicated task to analyze and evaluate the acquired welding defects images manually. Fortunately, deep learning has been successfully applied to image analysis and target recognition. However, the use of deep learning to identify we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(58 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…Here, the original annotation of public datasets is kept for a fair comparison with peer methods. For images with larger sizes, a sliding window can be used to process the image clip by clip [45]. Our original dataset is also included for testing:…”
Section: ) Datasetsmentioning
confidence: 99%
“…Here, the original annotation of public datasets is kept for a fair comparison with peer methods. For images with larger sizes, a sliding window can be used to process the image clip by clip [45]. Our original dataset is also included for testing:…”
Section: ) Datasetsmentioning
confidence: 99%
“…In particular, the MobileNet network was proposed as a lightweight network that requires less parameters and computation, but with better performance than certain deep networks with high complexity. In the MobileNet network, a new convolution method, called depthwise separable convolution, was proposed, which is widely used in image classification [67][68]. In recent years, researchers have made great efforts in remote sensing scene classification.…”
Section: Related Workmentioning
confidence: 99%
“…Total of 301 brain MRI images were used for the methods. The precision of the suggested methods varies from 94 to 96 percent.Haihong et al [16] suggested a new approach by integrating transfer learning and MobileNet to minimize time consumption and manual work required to evaluate welding defect images. GDXray, a public database was used to validate the method.…”
Section: Literature Reviewmentioning
confidence: 99%